Financial Technology in The Development of UMKM - Isnurrini Hidayat Susilowati (Enrichment : Journal of Management, 2020)
Digital technology is currently the main capital needed by industry players in developing their business. For the financial sector, technological innovation is not a new development for the industry. In financial technology (financial technology) it is known as FinTech. FinTech activities in financial services can be classified into 5 (five) categories, namely Payment, transfer, clearing, and settlement (payment, clearing and settlement). Micro, Small and Medium Enterprises (UMKM) have a big role as an effort to increase economic development in Indonesia. The role of FinTech in the development of MSMEs is to play a role in increasing financial literacy, increasing digital entrepreneurship and sources of business financing. One of the hopes for MSME players in business development is by accessing financing through Fintech in the form of Peer to Peer Lending (P2PL) after being inaccessible by banks.